2013
DOI: 10.1680/geolett.13.00064
|View full text |Cite
|
Sign up to set email alerts
|

Use of bacterial ureolysis for improved gelation of silica sol in rock grouting

Abstract: Low pH silica-based grouts suitable for penetrating fine aperture fractures are increasingly being developed for use in engineering applications. Silica sol has an initial low viscosity and mixing with an accelerator destabilises the suspension producing a gel. The influence of sodium, calcium and ammonium chloride accelerators on gel time, rate of gelation and shear strength of the resulting gel were investigated in this study. For the first time the potential use of bacterial ureolysis as an accelerator for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
2
0
1
Order By: Relevance
“…In the study by Cheng et al (2019) 30 , fermentative activity was established by inoculating soils with a mixed microbial culture obtained from activated sludge and provided in solutions containing alginate and glucose (pH initial = 7.5). Although using a different microbial pathway, Maclachlan et al (2013) 31 demonstrated that microbial urea hydrolysis could be used to mediate the gelation of initially acidic colloidal silica grouts through increases in solution ionic strength and pH. In this study, mediation of the process via ureolysis was found to achieve a more uniform gel structure, faster gelation, and a higher gel shear strength when compared to gels formed using chemical accelerants, albeit with the generation of aqueous ammonium resulting from urea hydrolysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study by Cheng et al (2019) 30 , fermentative activity was established by inoculating soils with a mixed microbial culture obtained from activated sludge and provided in solutions containing alginate and glucose (pH initial = 7.5). Although using a different microbial pathway, Maclachlan et al (2013) 31 demonstrated that microbial urea hydrolysis could be used to mediate the gelation of initially acidic colloidal silica grouts through increases in solution ionic strength and pH. In this study, mediation of the process via ureolysis was found to achieve a more uniform gel structure, faster gelation, and a higher gel shear strength when compared to gels formed using chemical accelerants, albeit with the generation of aqueous ammonium resulting from urea hydrolysis.…”
Section: Introductionmentioning
confidence: 99%
“…Collectively, outcomes from both studies suggest that microbial glucose fermentation activity can provide a viable pathway to control the gelation of colloidal silica grouts. Although similar in principle to the work by Maclachlan et al (2013) 31 , the use of glucose fermentation activity was expected to address limitations related to the use of microbial ureolysis by providing a method capable of improving soils under more acidic conditions and eliminating the production of ammonium by-products.…”
Section: Introductionmentioning
confidence: 99%
“…3.05×10 -7 3.21×10 -3 Whiffin (2004) 25) 2.00×10 -7 0.2 van Paassen (2009) 3) -0.055 Tobler et al (2011) 26) 1.15×10 -11 -6.32×10 -10 -Maclachlan et al (2013) 27) 8.33×10 -10 -2.22×10 -9 -Tobler et al (2014) 28) 1.92×10 -8 -Mahanty et al (2014) 29) 9.60×10 -12 -1.73×10 -10 -Lauchnor et al (2015) 30) 8.92×10 -8 0.305…”
unclassified